From division to dialogue: navigating stigmatization, polarization, and understanding in contentious politics - Biglow, Brandon (My University, 2026)
Modern society seems caught in a relentless cycle of division, where narratives of irreconcilable conflict dominate political discourse, portraying opposing groups not as contributors to a shared democratic project but as existential threats to one another. Stigmatization, as described by Erving Goffman, reduces individuals from “whole and usual persons” to “tainted” or “discounted” individuals, delegitimizing their voices in public discourse by framing disagreements as moral conflicts and marginalizing dissenting perspectives. Similarly, polarization, as Ezra Klein explains, hardens ideological and partisan identities, fostering group loyalty, mutual hostility, and an entrenched “us versus them” mentality. Contentious topics become not just difficult to discuss but nearly impossible, as compromise is dismissed and common ground obscured— outlining society’s broader failure to embrace collective understanding. The proliferation of information—whether misinformation or disinformation—distorts perceptions, reinforces polarized narratives, and simplifies complex issues towards binary solutions. This dynamic perpetuates stigmatization, deepens societal divides, and hinders constructive engagement within contentious political issues. This paper will argue that media sensationalism—driven by disinformation, misinformation, algorithms, and echo chambers reinforced through confirmation bias and our own unknowing prejudices—exacerbates stigmatization and polarization, deepening existing divides. However, this paper will challenge the narrative that marginalized and dissenting groups are as widely despised as media portrayals suggest, towards demonstrating that societal divisions are often less severe in reality. I propose a solution rooted in Gadamerian hermeneutics, emphasizing the fusion of horizons and the recognition of individual lived experiences as a foundation for fostering direct communication, rebuilding public discourse, and promoting understanding.
Keywords: stigmatization; modern society; politics; media sensationalism